2015
DOI: 10.1074/jbc.m115.661249
|View full text |Cite
|
Sign up to set email alerts
|

The Organophosphate Degradation (opd) Island-borne Esterase-induced Metabolic Diversion in Escherichia coli and Its Influence on p-Nitrophenol Degradation

Abstract: Background: Because of the mobile nature of the opd island, identical opd and orf306 sequences are found among soil bacteria. Results: In E. coli, Orf306 suppresses glycolysis and the TCA cycle and promotes up-regulation of alternate carbon catabolic operons. Conclusion:The up-regulated hca and mhp operons contribute to PNP-dependent growth of E. coli. Significance: Together with opd, orf306 contributes to the complete mineralization of OP residues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 32 publications
(41 reference statements)
0
14
0
Order By: Relevance
“…Propionate-dependent repression of co293 therefore abolishes translational inhibition of hcaR facilitating synthesis of abundant amounts of HcaR required for activation of the PP and HPP pathways [22]. We have previously shown involvement of the hca and MHP operons in p-nitrophenol catabolism [10]. The experimental evidence gained in the present study suggests that the PNPsupported growth of E. coli MG1165 (pSDP10) cells could be due to repression of co293 expression in the presence of Orf306.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Propionate-dependent repression of co293 therefore abolishes translational inhibition of hcaR facilitating synthesis of abundant amounts of HcaR required for activation of the PP and HPP pathways [22]. We have previously shown involvement of the hca and MHP operons in p-nitrophenol catabolism [10]. The experimental evidence gained in the present study suggests that the PNPsupported growth of E. coli MG1165 (pSDP10) cells could be due to repression of co293 expression in the presence of Orf306.…”
Section: Discussionmentioning
confidence: 62%
“…In silico analysis of Orf306-responsive sRNAs As described in our previous studies, we designed sense and antisense probes to identify ncRNAs made from each of the 2240 intergenic regions found in the genome of E. coli MG1655 [10]. The microarray data generated from these probes were then used to identify Orf306-responsive ncRNAs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In presence of MP, transcriptomic data reveals the induction of genes involved in several cellular processes, including genes that codify efflux pumps, porins, permeases, transcriptional regulators and transporters involved in multidrug resistance. Chakka et al (2015) reported that transcriptional regulation is not limited only to regulation of the genes involved in PNP degradation but to a whole set of metabolic and transcriptional processes. In this study, as a result of the presence of MP, different transcriptional regulator showed an induction, the number of these kinds of genes, that showed an overexpression increases as the culture time increases (two genes at 0 h, 29 genes at 3 h, and 41 genes at 9 h).…”
Section: Discussionmentioning
confidence: 99%
“…The ability to survive under difficult environmental conditions combined with the extensive knowledge on its genetics, transcriptome, proteome and metabolome makes Escherichia coli a well-established model organism for bacterial molecular studies (Idalia and Bernardo, 2017). The transcriptomic studies on the stress responses of E coli to pesticides such as glyphosate (Lu et al, 2013), paraquat (Allen and Griffiths, 2012) and p- nitrophenol (Chakka et al, 2015) were recently reported. Though CP is a widely used and moderately toxic insecticide with several reports on its bacterial degradation, the existing literature on the molecular mechanism aiding bacterial response to chlorpyrifos (CP) are scarce to none.…”
Section: Introductionmentioning
confidence: 99%